Moderating Effect of Self-Confidence Between General Communication and Mathematics Communication Skills - Gallego, Marian Kaye F.; Laguipo, Jeric John S.; Manatas, Clyde Joshua M.; Villanueva, Charles Fernand R. (CV. Tripe Konsultan, 2025)
This study investigated the interplay between general communication skills (GCS), mathematics communication skills (MCS), and self-confidence in mathematics (SCM) among Bachelor of Secondary Education major in Mathematics (BSEd–Math) students in the Philippines. Utilizing a quantitative, descriptive-correlational design, data were obtained from 104 BSEd–Math students at the University of Mindanao through convenience sampling. Spearman’s Rank Correlation Coefficient and regression analysis were employed to examine the relationships among the variables and to assess the potential moderating role of SCM. Findings indicate a non-significant correlation between GCS and MCS, suggesting the need for targeted pedagogical interventions to enhance mathematical communication skills among prospective mathematics educators. Moreover, SCM did not significantly moderate the relationship between GCS and MCS. These results emphasize the critical role of fostering both communication proficiency and mathematics confidence as integral components of teacher preparation. The study’s implications extend to instructional practice, highlighting the importance of interventions designed to strengthen problem-solving abilities and improve the clarity and precision with which mathematical concepts are conveyed in educational contexts